Cucumber mosaic virus populations in Tunisian pepper crops are mainly composed of virus reassortants with resistance‐breaking properties. (29th January 2013) - Ben Tamarzizt, H.; Montarry, J.; Girardot, G.; Fakhfakh, H.; Tepfer, M.; Jacquemond, M.
Abstract : Cucumber mosaic virus is one of the most prevalent viruses in Tunisian pepper crops, where it has been detected in 68% of plants developing mosaic symptoms, making it essential to characterize the molecular and biological properties of local CMV populations. Two hundred and seventy‐eight isolates collected in the late 1990s, 2006 and 2008–2010 were characterized genetically. Isolates belonging to the three phylogenetic subgroups of CMV (IA, IB and II) were detected, but surprisingly, 90% of the isolates were reassortants between subgroups IA and IB, with two predominant haplotypes, IB‐IA‐IA and IB‐IA‐IB (nomenclature according to the subgrouping of the three genomic RNAs). The IB‐IA‐IA haplotype was present in all regions surveyed, while IB‐IA‐IB was observed only in northern Tunisia. This situation was unexpected, because CMV reassortants were previously thought to be counterselected in nature, and this raises the questions of the origin of IB strains in Tunisia and of the widespread distribution of these two reassortant types. Phylogenetic studies revealed low diversity within haplotypes, whatever the locality or the year of sampling. However, analysis of haplotype frequencies revealed a high genetic differentiation between CMV populations, which was better explained by the localities of sampling than by years. Geographic distances affected the differentiation of CMV populations, mainly between north and central Tunisia. When tested against a polygenic resistance to CMV movement in pepper, 55 of 57 isolates tested were able to break the resistance, indicating that this resistance would not be useful for controlling CMV in Tunisian pepper fields.